Human Factors Evaluation of Conflict Resolution Advisories for Air Traffic Control in the En Route Domain. (September 2016) - Hah, Sehchang; Willems, Ben; Mueller, Gary; Johnson, Daniel R.; Woo, Hyun; DiRico, John; Hallman, Kevin; Schulz, Kenneth; Alvidrez, Sonia; Meyer, Karl A.; Bastholm, Robert; Rein, Jonathan R.; et al.
In this paper, we report results of a human-in-the-loop simulation experiment that evaluated how Conflict Resolution Advisories (CRA) affected en route air traffic controllers' performance. Twelve current en route Certified Professional Controllers from Air Route Traffic Control Centers (ARTCCs) participated in the experiment. Results showed that controllers used CRA menus significantly more often than Baseline menus. They also spent more time interacting with the CRA menus than with the Baseline menus. Most of the participants' subjective ratings favored the CRA, but they also pointed out a few features to be improved.